Limb specific training magnitude and asymmetry measurement to discriminate between athletes with and without unilateral or bilateral lower limb injury history. (July 2022) - Wylde, Matthew J.; Callaway, Andrew J.; Williams, Jonathan M.; Yap, Jeter; Leow, Shina; Yong, Low Chee
Abstract: Objectives: This study investigates the use of tibia-mounted inertial measurement units (IMUs) as an alternative to upper trunk-mounted IMUs for assessing lower limb training magnitudes and asymmetries in Badminton players. Design: Cross-Sectional Study. Setting: Youth athlete training environment. Participants: Thirty-three adolescent Badminton players, grouped based on injury history (non-injured = 19, bilateral = 6, unilateral = 8). Main outcome measures: Players wore 1 upper trunk-mounted and 2 tibia-mounted IMUs during simulated match-play. Modified vector magnitudes were assessed to identify if the IMUs can discriminate between injury history groups to assess the device location sensitivity, determine to what extent players exhibit movement asymmetry within the sport, and explore if asymmetries exist within groups with injury history. Results: Upper trunk-mounted IMUs could not distinguish between injury history groups. Statistically significant asymmetries were observed in the non-injured group, however these were below the 10% threshold for clinical asymmetry. No significant asymmetries were observed in the bilaterally injured group, while statistically significant asymmetries were observed in the unilaterally injured group, which were above the 10% threshold for clinical asymmetry. Conclusion: These results suggest that direct limb specific IMU measurement offers a method to suitably assess training magnitudes and asymmetry within a sporting performance, rather than isolated non-sport specific testing. Highlights: Upper trunk-mounted IMUs could not distinguish athletes based on injury history. Tibia-mounted IMUs detected significant asymmetries (<10%) in non-injured athletes. Significant asymmetries (>10%) were detected in unilaterally-injured athletes. Limb specific IMUs suitable to assess lower limb training magnitudes and asymmetry.